Development of a fuzzy expert system based on PCS 7 and FuzzyControl++, JES, ISSN: 2278–6538 - Hanane Zermane; Leila Hayet Mouss; Sonia Benaicha (Journal of Electronic Systems, 2012)
The basic idea of this work was to study the application of expert systems and fuzzy logic in the field of diagnostic and industrial maintenance. For this, a fuzzy expert system designed, developed and simulated in Ain Touta cement society in Batna in the East of Algeria. Dedicated to control cement mill. The application of fuzzy logic and expert systems to control the difference shown in the control system using fuzzy regulators for the operation of the grinding without unnecessary stops, it also helps the operator to know the maintenance task to perform. In addition, regulators decentralization allows the availability of fuzzy control, even if one of the regulators is absent, it does not prevent the other to complete its task to control fineness, mills temperature and feed.